Exercise for cardiovascular disease prevention and treatment : from molecular to clinical. Part 1 - Xiao, Junjie (Springer, 2017)
The book provides an intensive overview on exercise for cardiovascular disease prevention and treatment, from basic research to clinical practice. The volume firstly summarizes the acute and chronic response to exercise. Secondly, evidence for exercise as medicine for the heart based on clinical studies and basic research is summarized. Thirdly, molecular mechanisms mediating the beneficial effects of exercise including IGF-1-PI3K-AKT signalling, NO signalling, C/EBPB-Cited4 signalling, Non-coding RNAs, epigenetic regulators, mitochondria adaption and exosomes are presented. Finally, exercise dosing, prescription and future prospects are provided. This book will provide valuable reference for researchers in cell biology, physiology, as well as physician, physical therapist in cardiology, sport medicine, etc.
Keywords: Cardiovascular system -- Diseases -- Exercise therapy.; Cardiovascular system -- Diseases -- Prevention.; elektronické knihy; electronic books